Analysis of Environmental Economic Policy in Indonesia: A Literature Study on Environmental Economic Instruments in National Regulations - Teguh Permana; Andriani Puspitaningsih (Takaza Innovatix Labs Ltd., 2026)
This study examines environmental economic policies in Indonesia through a literature review and analysis of national regulatory documents. The main focus is on mapping environmental economic instruments regulated under Law No. 32 of 2009 on Environmental Protection and Management, Government Regulation No. 46 of 2017, PP 22/2021, the Presidential Regulation on Carbon Economic Value (NEK), and strategic planning documents such as RAN-GRK, LTS-LCCR, and RPJMN. The study employs a qualitative-descriptive approach, using thematic content analysis to identify categories of economic instruments, including market-based instruments, funding mechanisms, risk-based licensing, and incentive–disincentive schemes. Findings indicate that Indonesia has established a relatively comprehensive regulatory framework; however, its effectiveness remains limited due to regulatory inconsistencies, institutional capacity constraints, inadequate environmental data, and weak monitoring mechanisms. The study recommends enhancing inter-agency coordination, standardizing environmental data, developing digital monitoring systems, and expanding the implementation of carbon taxes and payment-for-environmental-services schemes. These findings are expected to contribute to the development of more effective environmental economic policies, supporting Indonesia’s transition toward a low-carbon economy